Influence of Home and Career on the Academic Performance of Married Distance Learners in South-West, Nigeria: Comfort Adeniyi, Esther Oladele, Emmanuel Adeniyi (PJDOL, 2023)
The paper examined the influence of Home and career on academic performance of married Distance Learners in South West, Nigeria. The study employed survey research design, one hundred and four (104) women and one hundred and thirty six (136) men were involved in the study, making a total of two hundred and forty married (240) Distance learners who were involved in the study. The sample for the study was selected using purposive sampling technique. The designed questionnaire was the instrument used with a reliability coefficient of 0.78. The data collected were analyzed using frequency counts, percentages, mean and standard deviation.